A nonlinear numerical scheme to simulate multiple wind effects on twin-box girder suspension bridges. (15th March 2019) - Zhou, Rui; Ge, Yaojun; Yang, Yongxin; Liu, Shiyi; Du, Yanliang; Zhang, Lihai
Highlights: A nonlinear numerical scheme was developed to simulate various wind effects on twin-box girder bridges in time domain. Wind tunnel tests were conducted to validate the calculated critical flutter wind speed of twin-box girder bridges under uniform flow (failure at 1/2L of the deck) and turbulence flow (failure at 3/4L of the deck). The flutter process of the bridge changes from the stable LCO of soft flutter to the unstable coupled divergence with symmetrical coupled oscillation. The vertical VIV of the bridge with the maximum amplitude of about 0.2 m and the 7th vertical mode belong to LCO with Hopf bifurcations. Abstract: The present study aims to investigate multiple wind effects on long-span twin-box girder bridges by developing a time-dependent nonlinear numerical scheme, which takes into account a range of aerodynamic forces, such as the stationary aerodynamic force, self-excited force, buffeting force and vortex-induced vibration (VIV) force. After calibration and validation, the developed scheme was implemented to investigate wind-induced behaviors of the Xihoumen Suspension Bridge. The results show that the developed scheme has the capability of simulating the nonlinear features of various types of bridge aerodynamic forces and can reproduced the flutter phenomenon from wind tunnel testing and the VIV phenomenon subject to field measurement. In addition, it predicts that, under the critical wind velocity (Ucr ) of 95 m/s in smooth flow, the failure mode of the bridge can be defined as the disconnection of hangers at the 1/2L of the main span, while under the Ucr of 85 m/s in turbulence flow, the failure of the bridge can be described as multiple hangers fracture at the 3/4L of the main span with the symmetrical bending-torsional coupled oscillation. Besides, the vertical VIV of the bridge with the maximum amplitude of about 0.2 m and the 7th vertical mode belong to limit cycle oscillation.